Strategi Pengembangan Wisata Snorkeling di Pantai Tanjung Benoa, Bali - Adhelia Fatimah Azzahra; I Wayan Restu; I Ketut Wija Negara (Fakultas Kelautan dan Perikanan Universitas Udayana, 2023)
The island of Bali as one of the icons of Indonesian tourism is famous for its natural potential, community hospitality, cultural values and the value of the natural beauty of the sea which is packaged in marine tourism attractions. Marine tourism is a tourism activity in the form of enjoying the beauty, uniqueness, comfort and other values of marine nature and other values and water sports including the provision of facilities and infrastructure as well as other services that are managed commercially. Tanjung Benoa is a marine tourism destination that is favored as a Tourist Attraction (ODTW) in Badung Regency with water sports, snorkeling and diving attractions. This study aimed to determine the current condition of snorkeling tourism and determined the strategy for developing snorkeling tourism at Tanjung Benoa Beach. The study was conducted from January 2021 to February 2021, using quantitative descriptive methods and data analysis using SWOT analysis. The results showed that the condition of tourist visits for integrated snorkeling activities in marine tourism attractions experienced a drastic decline as a result of the 2020-2021 COVID-19 pandemic conditions. The potential for marine tourism, especially snorkeling activities in Tanjung Benoa, is coral reefs, reef fish and other marine biotas. Based on the results of the SWOT analysis, Tanjung Benoa Beach was in quadrant II. The strategy for developing snorkeling tourism on the Tanjung Benoa beach was in quadrant II or the ST (Strength and Threat) strategy. The ST strategy included maintaining the condition of coral reefs and marine life and studying the reclamation of Benoa Bay. The next strategy was to increase village rules related to health protocols and e-commerce-based marine tourism marketing.